Variations in de novo donor-specific antibody development among HLA-DQ mismatches in kidney transplant recipients - Peenida Skulratanasak; Thidarat Luxsananun; Nuttasith Larpparisuth; Nalinee Premasathian; Attapong Vongwiwatana (PLoS ONE, 2025)
Background HLA-DQ antibodies are the most prevalent de novo donor-specific antibodies (dnDSAs) after kidney transplantation (KT). The immunogenicity and impact of each HLA-DQ mismatch on graft outcomes can vary considerably. Methods This retrospective cohort study investigated the prevalence and risk factors for dnDSA development in patients who underwent KT at Siriraj Hospital between 2006 and 2020 and had HLA-DQB1 mismatches. Our center employed a protocol for post-KT dnDSA surveillance. The impact of dnDSAs on late rejection and graft survival was evaluated. Results In our cohort of 491 KT recipients, 59 (12.02%) developed dnDSAs to HLA-DQB1 at a median time of 4.2 years after KT. The risk of dnDSA occurrence was significantly higher among recipients with HLA-DQ7 mismatch (HR: 2.8; 95% CI: 1.21–6.52; P = 0.017) and HLA-DQ9 mismatch (HR: 2.63; 95% CI: 1.11–6.27; P = 0.028). Recipients who developed dnDSAs were younger (P = 0.009), had higher rates of medication nonadherence (P = 0.031), had pre-KT panel reactive antibody levels above 20% (P = 0.044), and received non-tacrolimus immunosuppression (P < 0.001) compared to those without. Recipients who developed dnDSAs to HLA-DQ exhibited a significantly higher incidence of late graft rejection (HR: 7.76; 95% CI: 5–12.03; P < 0.0001) and inferior death-censored graft survival than those without dnDSAs (log rank P < 0.001). Conclusion The patients with HLA-DQ7 and HLA-DQ9 mismatches exhibit the highest risk of developing dnDSAs. Individualized immunosuppression adjustment and kidney allocation based on specific HLA-DQ mismatch may enhance long-term graft survival.